Establishment of haemorrhagic septicaemia in mice inoculated with water contaminated with pasteurella multocida type B:2 - Khaleel, Mohammed Muqdad (2014)
Haemorrhagic septicaemia (HS) is an infectious disease of cattle and buffalo inflicted by serotypes B: 2 and E: 2 of Pasteurella multocida in Asian and African countries respectively and characterised by an acute, highly fatal septicaemia with high morbidity and mortality. Therefore, the present study aims at evaluating the presence of P. multocida type B: 2 in various organs using Polymerase chain reaction (PCR), and host cell response in mice infected with Pasteurella multocida type B: 2 in contaminated river water with mice carcasses kept for 24, 48 and 72 hours. This study postulated that the outbreak of HS among buffaloes and cattle could be due to the consumption of river water contaminated with infected HS carcasses and the aerosol routes could perhaps be a readily available route for effective vaccine administration and heightened immunity in animals considering the progressive responses of APPs through this route. Sixty five healthy BALC male mice of eight to ten weeks old were used in this study. The wild-type P. multocida B: 2 used in this study were obtained from stock culture. The river water was obtained from Hulu Langat and was cultured to confirm that it was free from P.multocida type B: 2, Fifteen mice were initially inoculated with 1.0 mL of P. multocida type B: 2 intraperitoneally. Five infected mice carcasses were placed in each tank for 24,48 and 72 hours and1ml of the contaminated river water containing Pasteurella multocida type B: 2 were inoculated via the intraperitoneally and aerosol routes while, 0.4 ml of Pasteurella multocida type B: 2 was inoculated orally into five mice in each group and after 48 hours the mice were euthanized by cervical dislocation. Blood samples were collected directly from the heart into plain tubes from the moribund animals to obtain serum for the analysis of serum amyloid A (SAA) and haptoglobin. The fourth group is the control group comprised of five mice and was inoculated with 1.0 mL of sterile Phosphate Buffered Saline (PBS) pH7. Post mortem was conducted and the brain, kidney,heart, spleen, lungs and liver were sampled for histopathology. All the organs were cultured on the blood agar and incubated at 37°C for 24 hours. PCR was performed on the organs from the mice. The concentration of SAA increased significantly (p<0.05) in the mice that were infected with the contaminated river water for 72 hours followed intraperitoneal group compared to the control, oral and aerosol group. There were also significant increase (p<0.05) in the concentrations of Hp in the group of mice that were infected with contaminated river water for 24 hours intraperitoneally relative to the control, oral and the aerosol groups. The PCR results revealed the presence of P.multocida from the brain, kidney, heart, spleen, lung and liver in the group of mice from the intraperitoneal, oral and aerosol groups. The river water kept for 24 hours was positive for P. multocida in the intraperitoneal, oral and the aerosol groups. The river water kept for 48 and 72 hours were positive for P. multocida in the intraperitoneal and oral groups. The cellular changes in the vital organs include thrombosis, inflammatory cells, hemorrhage, degeneration and necrosis. In the brain, heart, kidney, liver, lung and spleen, the degeneration and necrosis was significantly high (p < 0.05) compared to the other cellular changes in the mice carcasses infected with P. multocida in contaminated river water kept for 72 hours. In conclusion, mice model could be used to enhance the understanding of the progression of the disease and control of the natural disease through the various routes of the disease transmission and contaminated river water infected with HS carcasses could be a potential source of infection if the carcasses are not removed from the river water immediately.